The Effect of Using the Picture Series Assisted Writing Relay Method on the Motivation and Narrative Writing Skills of Grade V Elementary School Students - Fatmawati F; Tarman A Arif; Haslinda H (Universitas Pendidikan Indonesia (UPI), 2022)
This research aims to determine the Impact of The Writing Relay Method Assisted by Series Drawing Media Application on the Motivation and Writing Narrative Skills of Class V Students at Morowa Cluster, Sinoa District, Bantaeng Regency. This research was quantitative research using quasi-experimental methods. The design used in this study was a quasi nonequivalent control group design. The population in this study were all students of grade V elementary school ftom 5 elementary schools at Morowa Cluster of Sinoa District of Bantaeng Regency, the samples were students of class V of SDN 37 Pa'rasangang Beru and students of class V of SDN 38 Janna -Jannaya. Data collection techniques were questionnaires and tests. The data analysis technique used was theindependent sample t-test and Monova Test, which was previously tested for prerequisites ie normality and homogeneity. The results of this study indicate the effect of motivation and skills in writing narrative that are given treatment in the form of the Relay Writing method with the help of serial picture media compared to students who are not given treatment. Based on the results of the independent sample t-test on hypothesis I, the sig value was obtained. of 0.002 0.05 then HO is rejected and H1 is accepted, in hypothesis II the sig value is obtained. of 0.001 0.05 then HO is rejected and H1 is accepted, and the results of the Monova test, obtained the value of Sig. 0.000 0.05, then HO is rejected and H1 is accepted.